Burning Bright Play Still - Broadhurst Theater:::Creator::::::::::::
From left to right: Mordeen (Barbara Bel Geddes), Joe Saul (Kent Smith), Victor (Martin Brooks), and Friend Ed (Howard De Silva) in the play adaptation of John Steinbeck's novella. This show closed after thirteen performances at the Broadhurst Theatre in New York. Digital copy only. No hard copy.